Modeling the excitation of graphene plasmons in periodic grids of graphene ribbons: an analytical approach - Gonçalves, Paulo André Dias (2016)
We study electromagnetic scattering and subsequent plasmonic excitations in periodic grids of graphene ribbons. To address this problem, we develop an analytical method to describe the plasmon-assisted absorption of electromagnetic radiation by a periodic structure of graphene ribbons forming a diﬀraction grating for THz and mid-IR light. The major advantage of this method lies in its ability to accurately describe the excitation of graphene surface plasmons (GSPs) in one-dimensional (1D) graphene gratings without the use of both time-consuming, and computationally-demanding full-wave numerical simulations. We thus provide analytical expressions for the reﬂectance, transmittance and plasmon-enhanced absorbance spectra, which can be readily evaluated in any personal laptop with little-to-none programming. We also introduce a semi-analytical method to benchmark our previous results and further compare the theoretical data with spectra taken from experiments, to which we observe a very good agreement. These theoretical tools may therefore be applied to design new experiments and cutting-edge nanophotonic devices based on graphene plasmonics.